The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1073/pnas.1809355115
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Larché–Cahn elasticity, a milestone of 20th-century thermodynamics

Abstract: SignificanceBy concatenating the fields of continuum mechanics and alloy thermodynamics in a unified framework, the theory of open system elasticity by Francis Larché and John W. Cahn achieved one of the key advances in thermodynamics of the 20th century. The theory’s implications for the coupling between stress and composition are generally well acknowledged, yet selected issues are under debate. It is, therefore, dissatisfactory that the predictions for the open system elastic parameters—as the theory’s cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Expressions for binary crystal structures are now available which extends the scope to a broad range of common crystal structures. In the future, it will be interesting to quantify the link to the thermodynamic description by Larché and Cahn and to calculate open system elastic constants 55 based on the long wavelength acoustic limit 39 . The additional finding of optical phonon modes goes beyond the theory of hydrodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Expressions for binary crystal structures are now available which extends the scope to a broad range of common crystal structures. In the future, it will be interesting to quantify the link to the thermodynamic description by Larché and Cahn and to calculate open system elastic constants 55 based on the long wavelength acoustic limit 39 . The additional finding of optical phonon modes goes beyond the theory of hydrodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Larché and Cahn (1973, 1978a, 1978b, 1982 has been hailed as "a milestone of twentieth century thermodynamics" (Shi et al, 2018). It has been applied successfully to the study of epitaxial thin films (e.g., Guyer & Voorhees, 1996;Lian et al, 2021;Spencer et al, 1991;Wang et al, 2006), lithium ion batteries (e.g., Bower et al, 2011;Cui et al, 2012;Meca et al, 2016;Sethuraman et al, 2010;Shi et al, 2018), and coherent precipitates in alloys (e.g., Kamachali et al, 2014Kamachali et al, , 2018Schwarze et al, 2017;Voorhees & Johnson, 1989). Here we briefly review the key concepts that underlie our work, noting that other recent studies also discuss these concepts from a variety of perspectives (e.g., Powell et al, 2018Powell et al, , 2019Voorhees & Johnson, 2004;Wheeler, 2018).…”
Section: Larché-cahn Theorymentioning
confidence: 99%
“…The work of Larché and Cahn (1973, 1978a, 1978b, 1982, 1985) has been hailed as “a milestone of twentieth century thermodynamics” (Shi et al., 2018). It has been applied successfully to the study of epitaxial thin films (e.g., Guyer & Voorhees, 1996; Lian et al., 2021; Spencer et al., 1991; Wang et al., 2006), lithium ion batteries (e.g., Bower et al., 2011; Cui et al., 2012; Meca et al., 2016; Sethuraman et al., 2010; Shi et al., 2018), and coherent precipitates in alloys (e.g., Kamachali et al., 2014, 2018; Schwarze et al., 2017; Voorhees & Johnson, 1989).…”
Section: Larché‐cahn Theorymentioning
confidence: 99%
“…A key complicating factor is the mutual interplay between these phenomena, i.e., the chemo-mechanical coupling between diffusing solutes and the stress fields around a precipitate, amplified by the small size of the precipitates. The importance of the chemo-mechanical coupling has been discussed in various contexts [ 1 , 2 , 3 , 4 , 5 , 6 ]. Recent theoretical and experimental studies have revealed that the mutual interactions between stress fields and solutal gradients at the precipitation front can alter precipitates’ growth and ripening kinetics [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%